2010
DOI: 10.1002/jid.1718
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment through ICT education, access and use: A gender analysis of Muslim youth in India

Abstract: Information and communication technologies (ICTs) developing countries can bridge socio-economic divides and empower the marginalised, including women and minority groups. This paper considers four dimensions of empowerment-psychological, social, educational and economic-and assesses benefits to each following computer education and usage of computer and Internet technology. Data were collected from 155 young Muslim women and men studying in three computer training centres in Mumbai, and a gender-based compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 15 publications
(15 reference statements)
1
22
0
Order By: Relevance
“…Khan and Ghadially (2010) and Techatassanasoontorn and Tanvisuth (2008) found that access to ICT services improve selfdetermination of users by making them aware of the choice they make and the impact thereof (e.g. the choice of staying away from criminal activities and the positive impact it could have on them) which concur with the finding.…”
Section: Discussion Of Findingssupporting
confidence: 54%
“…Khan and Ghadially (2010) and Techatassanasoontorn and Tanvisuth (2008) found that access to ICT services improve selfdetermination of users by making them aware of the choice they make and the impact thereof (e.g. the choice of staying away from criminal activities and the positive impact it could have on them) which concur with the finding.…”
Section: Discussion Of Findingssupporting
confidence: 54%
“…The author concludes that traditional discrimination in the fields of employment, income, and education turn the positive correlation between women and ICT into a negative one, if confounding variables are not accounted for. Thus, women seem to embrace digital technology more enthusiastically than men, and this has the potential to turn a vicious circle between low‐income and lacking education into a virtuous circle where women can reap economic empowerment gains (Hilbert ; Khan and Ghadially ). In a developed economy setting, Rice and Katz () found similarly that the “digital divide” is associated more with categories such as education and income rather than gender.…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%
“…Best and Maier (2007) evaluate the use of internet cafes and computer access points, noting that in rural India, women have unique patterns of computer use and internet access, particularly with respect to gender‐based scheduling issues. While statistics on gender and ICT in development remain underdeveloped (Hafkin and Huyer, 2007), evidence from Muslim communities in India shows that when male and female students have access to computers and the internet, female students take greater advantage of the technology than do male students and benefit more from it (Khan and Ghadially, 2010).…”
Section: Empirical Strategymentioning
confidence: 99%